Global environmental climate change, covid-19, and conflict threaten food security and nutrition - Hendriks, Sheryl L.; Montgomery, Hugh; Benton, Tim; Badiane, Ousmane; de la Mata, Gonzalo Castro; Fanzo, Jessica; Guinto, Renzo R *; Soussana, Jean-Francois (BMJ Publishing Group, 2022)
September 2021 saw the United Nations Food Systems Summit (UNFSS) take place in New York. It focused on the “three Cs” that are driving disruption to food systems and threatening recent progress in mitigating hunger, malnutrition, and undernutrition: global environmental climate change, covid-19 disease, and conflict. Summit delegates from 183 countries agreed that business as usual would not lead to the change necessary to achieve the sustainable development goals. Summit participants called for urgent action at scale.